What benefit–risk trade-offs are acceptable to rheumatoid arthritis patients during treatment selection? Evidence from a multicountry choice experiment - Carlomaurizio Montecucco; Rieke Alten; Robert Moots; Peggy Jacques; Helga Radner; Harald E Vonkeman; Nicolas Krucien; Sebastian Heidenreich; Katrien Van Beneden; Juan Carlos Nieto-González; Chiara Whichello (RMD Open)
Objective Understanding preferences of patients with rheumatoid arthritis (RA) can facilitate tailored patient-centric care. This study elicited trade-offs that patients with RA were willing to make during treatment selection.Methods Patients with RA completed an online discrete choice experiment, consisting of a series of choices between hypothetical treatments. Treatment attributes were selected based on literature review and qualitative patient interviews. Eligible patients were ≥18 years old, diagnosed with RA, receiving systemic disease-modifying antirheumatic drug therapy, and residents of Europe or USA. Male patients were oversampled for subgroup analyses. Data were analysed using a correlated mixed logit model.Results Of 2090 participants, 42% were female; mean age was 45.2 years (range 18–83). Estimated effects were significant for all attributes (p<0.001) but varied between patients. Average relative attribute importance scores revealed different priorities (p<0.001) between males and females. While reducing pain and negative effect on semen parameters was most important to males, females were most concerned by risk of blood clots and serious infections. No single attribute explained treatment preferences by more than 30%. Preferences were also affected by patients’ age: patients aged 18–44 years placed less importance on frequency and mode of treatment administration (p<0.05) than older age groups. Patients were willing to accept higher risk of serious infections and blood clots in exchange for improvements in pain, daily activities or administration convenience. However, acceptable trade-offs varied between patients (p<0.05).Conclusion Treatment preferences of patients with RA were individual-specific, but driven by benefits and risks, with no single attribute dominating the decision-making.